2020
DOI: 10.3389/fpls.2020.596000
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Profiles of Two Hydroponically Grown Sweet Basil Cultivars as Affected by the Composition of the Nutrient Solution and the Inoculation With Azospirillum brasilense

Abstract: Sweet basil (Ocimum basilicum L.) is one of the most produced aromatic herbs in the world, exploiting hydroponic systems. It has been widely assessed that macronutrients, like nitrogen (N) and sulfur (S), can strongly affect the organoleptic qualities of agricultural products, thus influencing their nutraceutical value. In addition, plant-growth-promoting rhizobacteria (PGPR) have been shown to affect plant growth and quality. Azospirillum brasilense is a PGPR able to colonize the root system of different crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 96 publications
3
16
0
Order By: Relevance
“…Moreover, several species have been reported to have enhanced growth and development in plants fertilized with different nitrogen concentrations or inoculated with PGPR in hydroponics [11,[16][17][18][19]. The data obtained showed that the effects of different nitrogen concentrations on lettuce sprayed with PGPR were consistent with previous reports, with plant growth showing an increasing trend [11,20]. Azotobacter sprayed lettuce increased vegetative growth expressed in number of leaves, fresh and dry weight of head, leaf and canopy area.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, several species have been reported to have enhanced growth and development in plants fertilized with different nitrogen concentrations or inoculated with PGPR in hydroponics [11,[16][17][18][19]. The data obtained showed that the effects of different nitrogen concentrations on lettuce sprayed with PGPR were consistent with previous reports, with plant growth showing an increasing trend [11,20]. Azotobacter sprayed lettuce increased vegetative growth expressed in number of leaves, fresh and dry weight of head, leaf and canopy area.…”
Section: Discussionsupporting
confidence: 84%
“…In general, plants produce natural defense substances like PSC after biotic or abiotic stress exposure, mainly depending on plant genotype, but their expression may be modulated by various different agronomic and environmental factors, including crop interaction with rhizosphere microbes [ 135 , 136 ]. For instance, the metabolomic analyses disclosed a clear link between AMF and PGPR inoculation in pepper and basil respectively, increased crops yield and the accumulation of several PSC associated with crop defense to environmental stresses [ 75 , 138 ]. Similarly, the metabolome analysis revealed that olive growing in fields where no-tillage and crop residue cover were applied, shown higher PSC concentration in xylem sap [ 139 ].…”
Section: Implications Of Soil Biodiversity For Nutrition and Food Safetymentioning
confidence: 99%
“…The growth enhancements brought about by PGPR can be the result of either indirect actions (e.g., preventing the harmful effects of phytopathogenic organisms via the production of antagonistic substances or thanks to the stimulation of the plant systemic resistance), or direct mechanisms, such as the production of bioactive molecules (e.g., phytohormones) and/or enhancing the nutrient bioavailability at the rhizosphere (Crecchio et al, 2018). Several pieces of research have also highlighted that PGPR might contribute to improve plants growth by increasing their tolerance to abiotic stressors (Jetiyanon and Kloepper, 2002;Zhang et al, 2008aZhang et al, , 2010Dimkpa et al, 2009;Chithrashree et al, 2011;Marastoni et al, 2019) and by modulating the physiological and biochemical activities of plants, especially those underlying the acquisition of mineral nutrient (Zhang et al, 2008b;Xie et al, 2009;Pii et al, 2015bPii et al, , 2016bPii et al, , 2018Scagliola et al, 2016;Kolega et al, 2020). In this context, the employment of PGPR, alone or in combination with synthetic fertilizers, with the aim of enhancing nutrients acquisition in plants and, more in general, of increasing the use efficiency of endogenous soil sources of nutrients, might help to shrink the use of agrochemicals, as also foreseen by the green deal concept for an increasingly sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that PGPR inoculation in crops has been shown to impact the production of secondary metabolites, thus affecting the overall nutraceutical value of the primary agricultural products. Indeed, several authors assessed that PGPR inoculation positively affected the quality of both fruit (e.g., mulberry, strawberry, citrus, apricot sweet cherry, and raspberry) (Eşitken et al, 2002(Eşitken et al, , 2003(Eşitken et al, , 2005(Eşitken et al, , 2006Orhan et al, 2006;Pii et al, 2018) and aromatic herbs (Banchio et al, 2009;Erika et al, 2010;Santoro et al, 2011;Heidari and Golpayegani, 2012;Cappellari et al, 2013Cappellari et al, , 2019aKolega et al, 2020) in terms of health-promoting compounds. However, very often the effects produced by PGPR inoculation on plant growth as well as on the qualitative and quantitative profile of secondary metabolites have been observed to be strongly dependent on the specific combination of plant species, microbial strain, and cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%